Validation of GLIM criteria for hospital malnutrition diagnosis by comparison of three different anthropometric approaches to evaluate reduced muscle mass: a prospective cohort study - Jazinaki, Mostafa Shahraki; Safarian, Mohammad; Arabi, Seyyed Mostafa; Jamali, Jamshid; Norouzy, Abdolreza (Frontiers in Nutrition, 2024)
Background and aim The Global Leadership Initiative on Malnutrition (GLIM) recently proposed a new malnutrition diagnostic tool known as the GLIM criteria. The GLIM criteria need confirmed validation before being widely used in each population or healthcare system. This study aimed to investigate the validation of the GLIM criteria for malnutrition diagnosis in hospitalized patients. Methods The content validity was assessed by calculating the content validity ratio (CVR) and content validity index (CVI). Subjective global assessment (SGA) is considered the reference tool to diagnose malnutrition in concurrent validation. In addition, the Kuder–Richardson 20 was used to evaluate the reliability of the GLIM criteria. Furthermore, hospital mortality, length of hospitalization (LOS), prolonged hospital stays (LOS >6 days), 30-day hospital readmission, and 30- and 60-day mortality were identified as malnutrition-related outcomes in predictive validity. Results A total of 332 adult/elderly hospitalized patients (median age: 58 (IQR: 24.7), 60.5% men) were enrolled to present the study. Appling GLIM criteria by considering the calf circumference < 31 cm in both genders or mid-upper arm (MUAC) < 23 cm in men and MUAC <22 cm in women as reduced muscle mass had an appropriate accuracy (84.6 and 83.4%, respectively), good ability to distinguish malnourished patients (AUC ROC: 0.85 and 0.83, respectively), satisfactory sensitivity (89.58 and 84.02%, respectively), and satisfactory specificity (81 and 83%, respectively) compared to the SGA tool. Furthermore, the reliability of the GLIM criteria for malnutrition diagnosis in hospitalized patients was acceptable in all 3 applied approaches (KR-20 > 0.5). The malnutrition diagnosed by GLIM criteria could significantly predict the odds of prolonged hospital stays, 30-day hospital readmission, and 60-day mortality, while it had no significant association with the risk of hospital mortality. Conclusion The current study revealed that applying GLIM criteria had satisfactory validity in diagnosing hospital malnutrition in non-critically ill hospitalized patients.